Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania